Tinjauan Hukum Atas Perlindungan Pemilik Rumah Kontrakan (Lex Jurnalica, 2010)
The practice of leasing a house plot is more often done based on the principle of faith alone and rarely use the terms black and white binding. So that the parties did not know the details and certainly nothing are its rights and obligations. Especially when there is dispute as a result wanprestasinya by one party, the other will be in a weak position and generally kontrakanlah homeowners who are in a weak position. Issues to be raised in this study, namely: How is legal protection for homeowners who rent out a house rented rented to tenants verbally, how the settlement of disputes between the owner of the rented house with a tenant does not pay rent associated with the rented house, and how responsibility for the maintenance of the rented house leased by tenants of the owner of the rented house. This study uses Normative Empirical Research Methods. The results show, the lease rental house is done verbally in terms of evidence is very weak. In the event of disputes between landlord and tenant house associated with the failure to pay rent by the tenant, to put forward the deliberations and communications of peace, although often the aggrieved homeowners. In terms of responsibility for the maintenance of the rented house, the dominant owner is responsible for heavy damages, while the tenant is responsible only limited to home maintenance, which is limited to clean up the environment.Keywords: Protecting, Home, Rental